Exploring the role of halide mixing in lead-free BZA2SnX4 two dimensional hybrid perovskites. Issue 4 (3rd January 2020) - Pisanu, Ambra; Coduri, Mauro; Morana, Marta; Ciftci, Yasemin O.; Rizzo, Aurora; Listorti, Andrea; Gaboardi, Mattia; Bindi, Luca; Queloz, Valentine I. E.; Milanese, Chiara; Grancini, Giulia; Malavasi, Lorenzo
Abstract : The role of halide substitution in a lead-free 2D hybrid perovskite is studied on the BZA2 SnX4 (BZA = benzylammonium; X = Cl, Br, I) system, by reporting the two novel compositions BZA2 SnBr4 and BZA2 SnCl4 . Abstract : The role of halide substitution in a lead-free 2D hybrid perovskite is investigated on the BZA2 SnX4 (BZA = benzylammonium; X = Cl, Br and I) system, by reporting the synthesis and the structural analysis by means of single-crystal X-ray diffraction data of the two novel compositions BZA2 SnBr4 and BZA2 SnCl4 . In addition, the mixed composition BZA2 Sn(Br x I1− x )4 (0 ≤ x ≤ 1) has been prepared by mechanochemical synthesis confirming the existence of a wide solid solubility between the two end-members. The absorption and emission spectra revealed a wide tuning of the band-gap by changing the halide, covering more than 300 nm in the visible range. Combined experimental and DFT calculations provide a complete picture of the electronic and structural properties of the BZA2 SnX4 system, revealing a strong influence of the halide on the orientation for the benzylammonium cation, on the hydrogen bonding system within the perovskite network, and on the distortion of the octahedra.